2022
DOI: 10.1007/s00170-022-10182-7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of thermal quantities for improving remote laser welding process capability space with consideration to beam oscillation

Abstract: This research aims to explore the impact of welding process parameters and beam oscillation on weld thermal cycle during laser welding. A three-dimensional heat transfer model is developed to simulate the welding process, based on finite element method. The results obtained from the model pertaining to thermal cycle and weld morphology are in good agreement with experimental results found in the literature. The developed heat transfer model can quantify the effect of welding process parameters (i.e. heat sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…5) deriving from a Gaussian heat distribution. This allowed the following formulations to be used [Mohan et al 2022]:…”
Section: Conical Laser Heat Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…5) deriving from a Gaussian heat distribution. This allowed the following formulations to be used [Mohan et al 2022]:…”
Section: Conical Laser Heat Sourcementioning
confidence: 99%
“…Further, to make the approach more realistic, boundary conditions -due to both contact with the air and contact with the workbench -have been added for the surfaces in question, finally achieving Cauchy-Stefan-Boltzmann boundary conditions. Once verified that the proposed model is well-posed (via hypothesis testing of a well-known result of the recent literature [Miranville et al 2021]) and reinforced by the fact that it does not allow the explicit recovery of T (x, t), an optimized Galerkin-FEM approach (to reduce the computational load useful for any real-time applications) has been implemented in MatLab R2022 PDE Tool and tested for the resolution of the problem by also selecting appropriate formulations of laser heat source, according with known experimental evidence [Mohan et al 2022].…”
Section: Introduction To the Problemmentioning
confidence: 99%
“…The numerical study is based on our previously developed laser welding model [12][13][14][15] which is described by the solutions of mass, momentum, and energy conservation equations [16]. The difference within this study lies in the definition of the laser heat distribution from the volumetric and hybrid heat sources.…”
Section: Numerical Modelmentioning
confidence: 99%
“…They did this by constructing joints out of AZ31 and AZ91 respectively [20]. It was revealed that joints with a certain distribution of phase grain architectures were generated in the middle of the stir zone when the tool was spun at 1400 revolutions per minute and the traverse rate was set to 25 millimeters per minute [21,22]. The setting for the traverse rate was 25 millimeters per minute.…”
Section: Introductionmentioning
confidence: 99%